The endangered White's seahorse Hippocampus whitei chooses artificial over natural habitats. Issue 2 (30th May 2019) - Simpson, Michael; Morris, Rebecca L.; Harasti, David; Coleman, Ross A.
Abstract: To explore whether the endangered White's seahorse Hippocampus whitei would choose to inhabit artificial over natural habitats, 10 adult H. whitei individuals were put through a series of binary choice trials in aquaria, during which they were offered different paired combinations of natural (different types of macroalga and seagrass) and artificial habitat (panels of swimming‐net material). It was found that H. whitei displayed a significant choice for swimming‐net material over all other available natural habitats and chose habitats according to the following rankings: (a) Net; (b) Sargassum sp.; (c) Posidonia australis ; (d) Zostera muelleri. Hippocampus whitei 's choice of swimming net material over natural habitat suggests that these artificial structures could be a useful conservation measure for seahorses in areas where natural habitat is becoming less favourable due to declines in abundance or quality.